2010
DOI: 10.1007/s11671-010-9579-0
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Monodisperse In-Doped ZnO Nanocrystals

Abstract: A method for the synthesis of high quality indium-doped zinc oxide (In-doped ZnO) nanocrystals was developed using a one-step ester elimination reaction based on alcoholysis of metal carboxylate salts. The resulting nearly monodisperse nanocrystals are well-crystallized with typically crystal structure identical to that of wurtzite type of ZnO. Structural, optical, and elemental analyses on the products indicate the incorporation of indium into the host ZnO lattices. The individual nanocrystals with cubic stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…To further reduce the size of ZnO tetrapods, the alcoholysis of zinc stearate was attempted to prepare ZnO tetrapods <100 nm in size. Growth of ZnO nanocrystals through the reaction of zinc stearate with alcohol in hydrocarbon solvents (noncoordinating solvents) under elevated temperatures was chosen because the nanocrystals resulting in this system were stable at room temperature, and no aggregation or oriented attachment was observed [47,48]. Jin [49,50] found that in the synthesis of ZnO nanocrystals, the introduction of Mg dopants significantly influenced the growth of the host lattices by modifying the crystallographic phase of ZnO seeds, which eventually led to a dramatic shape [60,61] reported ZnO tetrapods composed of core and legs with the same WZ structure.…”
Section: Nonhydrolytic Alcoholysis Routementioning
confidence: 99%
“…To further reduce the size of ZnO tetrapods, the alcoholysis of zinc stearate was attempted to prepare ZnO tetrapods <100 nm in size. Growth of ZnO nanocrystals through the reaction of zinc stearate with alcohol in hydrocarbon solvents (noncoordinating solvents) under elevated temperatures was chosen because the nanocrystals resulting in this system were stable at room temperature, and no aggregation or oriented attachment was observed [47,48]. Jin [49,50] found that in the synthesis of ZnO nanocrystals, the introduction of Mg dopants significantly influenced the growth of the host lattices by modifying the crystallographic phase of ZnO seeds, which eventually led to a dramatic shape [60,61] reported ZnO tetrapods composed of core and legs with the same WZ structure.…”
Section: Nonhydrolytic Alcoholysis Routementioning
confidence: 99%
“…In our experiments, we found that indium oxide seeds may form prior to the injection of alcohol to the initial reactions to grow the host ZnO nanocrystals because of the unintentional hydrolysis of the indium precursors at high temperature. Furthermore, indium precursor with reactivity much higher than that of zinc precursor may also lead to individual nanocrystals with cubic structures [38]. In this regard we designed a new synthetic scheme in which a solution containing metal precursors is injected into a high temperature solution containing alcohol.…”
Section: The High Temperature and Nonaqueous Approachmentioning
confidence: 99%
“…It is well known that the electrical conductivity of ZnO-based TCOs can be significantly improved via the incorporation of aluminium [39,66], gallium [67,68], or indium [38,69]. Hammarberg, et al prepared suspensions of In 3+ doped ZnO and Al 3+ doped ZnO nanocrystals in diethylene glycol by means of microwave heating [69].…”
Section: N-typementioning
confidence: 99%
See 1 more Smart Citation
“…25 Thus, the conductivity of the former is larger than that of the latter. Wang et al 26 have reported to have synthesized monodisperse indium-doped ZnO nanocrystals of size ca.10 nm and advocate incorporation of indium into the host ZnO lattice. But their highresolution transmission electron micrograph (HRTEM) analysis shows the presence of cubic In 2 O 3 nanocrystals among nanocrystalline hexagonal ZnO.…”
Section: Introductionmentioning
confidence: 99%